Evaluation of the male and female fertility and teratogenic effects of Lignosus rhinocerotis (Cooke) Ryvarden in rats - Zati Bayani Hamzah; Bushra Solehah Mohd Rosdan; Nurul Asma Abdullah; Wan Ezumi Mohd Fuad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Lignosus rhinocerotis (Cooke) Ryvarden (LR) or tiger milk mushroom has traditionally been used in Malaysia due to its abundant medicinal properties. The potential effects of LR on the male and female fertility and teratogenicity were investigated on rats. Male Sprague Dawley (10 rats/group) were orally administered with 0, 250, 500 and 1000 mg/kg/day of LR extract for 30 consecutive days. Female (5 rats/group) received the same treatment beginning the dioestrus of pre-mating, through mating periods and continuously up to day 20 of pregnancy while the rest of the females (5 rats/group) were left untreated. Evaluation on general health, behaviour, body weight and organ weights; reproductive and internal organs were carried out. Male fertility parameters such as the reproductive performance and hormones as well as sperm analysis were examined. Maternal gross assessment at autopsy and detailed foetal examination were conducted to determine the teratogenicity. The findings obtained on the male animals showed that no significant deleterious effects on the general health, body weight, reproductive and visceral organs weight, reproductive performance, hormones and sperm analysis of up to 1000 mg/kg/day daily doses of LR. Foetal parameters and gross examination of pregnant dams at autopsy showed that the extract did not affect the fertility of the rats and teratogenicity of the litters. Our findings showed that no treatment-related toxicity on the fertility of male and female rats in all groups following LR treatment. The herbal extract also did not result in teratogenic effects on the offspring of the treated dams.